EVALUASI KEBIJAKAN BUPATI TABALONG TENTANG BUM DESA DARI PERSPEKTIF SOSIAL DAN EKONOMI - Akhmad Badarudin (stiatabalong.ac.id, 2024)
Masingai II Village still has a population living below the poverty line, which is a government responsibility in policy-making. The objective of this study is to analyze and obtain a specific description of the success of the Tabalong Regent's Policy on Village-Owned Enterprises (BUM Desa) from a social and economic perspective in Masingai II Village, Upau District, Tabalong Regency. The research method used is descriptive qualitative, employing a qualitative approach where data sources were selected through purposive sampling, and data collection was conducted through interviews with 5 informants and documentation. The results of this study indicate that the Tabalong Regent's Policy on BUM Desa from a social and economic perspective (Case Study of Village-Owned Enterprises (BUM Desa) in Masingai II Village, Upau District, Tabalong Regency) has been successfully implemented. This is evident based on, evaluated through five assessment indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. From a social perspective, this policy has successfully brought about positive changes in the attitudes of the Masingai II community, and from an economic perspective, it has created job opportunities, increased the market value of products, and improved the income of the Masingai II Village community. The implications of this study highlight the need for policies to consider outcomes such as social and economic impacts. Keywords: Policy Evaluation, Village-Owned Enterprises, Social, Economic